Important Aspects of Evaluating the Foundations of the Development of Civil Society Institutions - Masharipov, Ikramjon Batirovich (European Journal of Life Safety and Stability (2660-9630), 2023)
The article analyzes the process of building a civil society, the features of indices for assessing the development of civil society in a number of countries, as well as some of the author's conclusions on improving the indices for assessing civil society.